Optimal Outcomes for Acute Avulsion Fracture of the Achilles Tendon Treated With the Insertional Reattachment Technique: A Case Series of 31 Cases With Over 2 Years of Follow-up. Issue 12 (October 2019) - Pi, Yanbin; Hu, Yuelin; Jiao, Chen; Ao, Yingfang; Guo, Qinwei
Background: Avulsion fracture of the Achilles tendon is a less common but debilitating disorder. There is a paucity of literature on this problem. Purpose: To present a retrospective case series assessing the clinical outcomes of avulsion fracture of the Achilles tendon after a reattachment procedure and to identify potential factors predicting postoperative outcomes. Study Design: Case series; Level of evidence, 4. Methods: A consecutive case series of 35 patients with acute insertional rupture of the Achilles tendon who received a reattachment procedure between 2011 and 2017 were reviewed. All patients were measured and classified by magnetic resonance imaging (MRI) and surgical findings. Patient-reported outcomes were evaluated using the visual analog scale (VAS) for pain, American Orthopaedic Foot & Ankle Society (AOFAS) Ankle-Hindfoot Scale, Foot Function Index (FFI), Tegner score, and Ankle Activity Score (AAS). The range of motion and single-legged heel raise test were also conducted for both ankles. Results: Thirty-one out of 35 (88.57%) patients were followed up for an average of 43.65 months. The VAS pain score and AOFAS Ankle-Hindfoot score improved from 4.87 ± 1.61 preoperatively to 2.07 ± 1.57 postoperatively and from 58.32 ± 18.66 preoperatively to 87.32 ± 7.53 postoperatively, respectively (both P < .001). The mean FFI, AAS, and Tegner scores after the operation were 11.84 ± 1.62, 5.71 ± 2.18, and 4.61 ± 1.31, respectively. Compared with the intact ankle, the mean deficit in dorsiflexion in the involved ankle was 9.54°± 6.25° (range, 0.59°-23.70°; P < .001) and the mean deficit in plantarflexion in the involved ankle was 6.31°± 4.02° (range, 0.24°-14.92°; P < .001). Thirty patients could perform the single-legged heel raise on the operative leg. A larger body mass index was associated with worse postoperative AOFAS and FFI outcomes. Longer follow-up predicted statistically significantly better FFI scores. Better postoperative dorsiflexion was associated with better postoperative FFI, AAS, and Tegner scores, and a statistically significant interaction was found between the VAS score and plantarflexion deficit. Age, preoperative insertional tenderness, Haglund deformity, and MRI classification showed little association with postoperative outcomes. Conclusion: This study demonstrated that the reattachment procedure for acute avulsion fracture of the Achilles tendon can achieve firm fixation and promising outcomes.